Cross‐species transmission of retroviruses among domestic and wild felids in human‐occupied landscapes in Chile. (27th January 2021) - Sacristán, Irene; Acuña, Francisca; Aguilar, Emilio; García, Sebastián; José López, María; Cabello, Javier; Hidalgo‐Hermoso, Ezequiel; Sanderson, Jim; Terio, Karen A.; Barrs, Vanessa; Beatty, Julia; Johnson, Warren E.; et al.
Abstract: Human transformation of natural habitats facilitates pathogen transmission between domestic and wild species. The guigna ( Leopardus guigna ), a small felid found in Chile, has experienced habitat loss and an increased probability of contact with domestic cats. Here, we describe the interspecific transmission of feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) between domestic cats and guignas and assess its correlation with human landscape perturbation. Blood and tissue samples from 102 free‐ranging guignas and 262 domestic cats were collected and analyzed by PCR and sequencing. Guigna and domestic cat FeLV and FIV prevalence were very similar. Phylogenetic analysis showed guigna FeLV and FIV sequences are positioned within worldwide domestic cat virus clades with high nucleotide similarity. Guigna FeLV infection was significantly associated with fragmented landscapes with resident domestic cats. There was little evidence of clinical signs of disease in guignas. Our results contribute to the understanding of the implications of landscape perturbation and emerging diseases.